(untitled) (Journal of the College of Basic Education, 2022)
The negative effects of electromagnetic radiation from cellular phones are not announced due to the fact that these effects take a relatively long time to appear and spread, as well as the installation of broadcasting towers is done without taking into account the technical, health and environmental conditions, that the emergence of various diseases and the emergence of the causal relationship between these diseases And between the non-ionizing radiation emitted by these mobile phones and the service transmission towers through the results of recent research, as well as the popularity of alerts about the necessity of keeping the mobile device away from the human body during use, with the emergence of many technical and health standards that must be observed when erecting the towers. The study found that the amount of damage to these rays located in the study area depends on several factors, the most important of which is the intensity of the radiation, its frequency and the time period of exposure to it, and given that the exposure to these rays is intermittent and over relatively spaced periods of time, the health effect of it is cumulative and does not result in immediate or immediate damage. Instantaneous, and of concern is the extent of the actual effect of these rays on the so-called blood-mental barrier, as when a momentary change occurs in the degree of permeability of this barrier, severe damage can result, which leads to the impossibility of obtaining an effective concentration of protein bodies in the cerebrospinal fluid in the head as well as The spread of different types of cancers in varying proportions, and the great effect of this rays is shown through birth defects, which are structural, behavioral, functional, and metabolic diseases that exist at birth and many other effects, leading to determining the conclusions and arranging the sources.